2015
DOI: 10.1007/s10384-015-0413-1
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour efficacy of preservative-free tafluprost for open-angle glaucoma patients, assessed by home intraocular pressure (Icare-ONE) and blood-pressure monitoring

Abstract: Icare-ONE enables glaucoma patients to measure their own diurnal IOP fluctuations. Patient-measured Icare-ONE IOP readings showed that PF tafluprost effectively reduced diurnal IOP in eyes with POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…In glaucoma patients, the iCare HOME allowed detection of changes to intraocular pressure following initiation of treatment with a prostaglandin analog. Cho et al 38 investigated the effect of once-daily treatment with tafluprost 0.0015% ophthalmic solution on patients with primary open angle glaucoma, with iCare ONE self-tonometry, and found that intraocular pressure was significantly reduced following 2 weeks of treatment. This study suggests that intraocular pressure reduction and hence treatment effect could be measured following only a single day of treatment, with a slight further reduction on the second day.…”
Section: Discussionmentioning
confidence: 99%
“…In glaucoma patients, the iCare HOME allowed detection of changes to intraocular pressure following initiation of treatment with a prostaglandin analog. Cho et al 38 investigated the effect of once-daily treatment with tafluprost 0.0015% ophthalmic solution on patients with primary open angle glaucoma, with iCare ONE self-tonometry, and found that intraocular pressure was significantly reduced following 2 weeks of treatment. This study suggests that intraocular pressure reduction and hence treatment effect could be measured following only a single day of treatment, with a slight further reduction on the second day.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Medical treatment with prostaglandin analogs or surgical procedures, such as trabeculectomy are most commonly used to decrease IOP. [4][5][6][7] In general, operative treatment is indicated for cases in which sufficient reduction of IOP cannot be achieved with medical treatment alone. 8 As the ultimate goal of glaucoma treatment is the maintenance of visual function for the rest of the patient's life, many patients undergo long-term administration of glaucoma eye drops.…”
mentioning
confidence: 99%
“…In addition, postoperative application of brinzolamide combined with timolol eye drops in the treatment of NVG patients can effectively reduce IOP and control its uctuations, and these effects are mainly achieved by regulating the balance of angiogenesis promoting/inhibiting factors, VEGF and its receptors. [20][21]. In this study, it was found that the visual acuity level of the patients was signi cantly increased after treatment, and the levels of VEGF and its receptors in the serum were signi cantly decreased, and the above situation is more obvious in the patients of the observation group, suggesting that the obvious curative effect of Ta oprost on patients with primary open angle glaucoma may be related to the improvement of vascular endothelial functional molecules.…”
Section: Of Changes In Hemorheological Parameters After Ta Uprost Tre...mentioning
confidence: 60%